Dispositivo eletrônico de baixo custo como instrumento de avaliação na reabilitação da mão parética de pacientes acometidos por acidente vascular encefálico - AZEVEDO, Priscila da Silva (2023)
INTRODUCTION: Brain injuries, such as stroke, result in neurological deficits of varying severity, which generally damage the extremities of the limbs and may lead to the individual's dependence on different activities of daily living. Under these conditions, technological assessment tools that combine precision of results, interactivity and motivational appeal are interesting to occupational therapy interventions. OBJECTIVE: To compare and measure the efficacy of a low-cost virtual device based on the human-computer interface as an evaluation tool in the rehabilitation of the hand of stroke survivors. Method: Quantitative, descriptive, clinical and randomized clinical trial. Sample: 13 individuals between 30 and 78 years old, of both sexes. Divided into the groups: clinical (GC1), n = 3 (AVE patients), and control (GC2), n = 10 (healthy volunteers). Each group was submitted to the protocol of procedures over 10 weeks (1st week: admission, 5th week: reassessment, and 10th week: discharge). Each week, in a single session, up to three attempts bilaterally were performed to obtain mean values of muscle strength (MCR and dynamometry), ADM (goniometer), sensory perception (esteiometer), and Functional Independence Measure (MIF) were compared with the registers of the Data Glove. Only GC1 received rehabilitation interventions in Occupational Therapy between the evaluation times. GC2 only went through data collection in the three defined times. Statistical analysis: ANOVA, Fischer post-test - p <0.05. Column charts (mean ± standard deviation), GraphPad Prism 6.0. RESULTS: The findings suggest that: muscle strength (MCR), sensory perception and GCM flexion ROM improved significantly. Muscle strength (dynamometer) showed subtle improvement. MIF shows functional recovery in the GC¹. The data glove manages to gather in its graphs results inferred by the physical tests, and functional. CONCLUSION: It is suggested that the Data Glove is a promising technological tool to measure patient gains during rehabilitation and can record differences in functional and physical damage in stroke survivors.